Integrasi Digital Marketing dan Pengalaman Pelanggan Dalam Community-Based Cafe - Noor Khairiyyah; M Adhitya Nugraha Pratama; Qudwatun Niswah; Muhammad Sulton (Forum Kerjasama Pendidikan Tinggi, 2026)
The development of digital marketing has encouraged culinary businesses to move beyond promotional activities toward creating meaningful customer experiences. This phenomenon can be observed at Cafe 0 KM, which utilizes digital platforms as a medium to foster customer engagement and build a community amid increasingly intense competition in the cafe industry. This study aims to explore how the integration of digital marketing and customer experience contributes to the formation of a community-based relationship at Cafe 0 KM. A qualitative approach with a case study design was employed in this research. Data were collected through in-depth interviews with key informants, direct observation, and supporting documentation. The data were analyzed using thematic analysis through processes of data reduction, categorization, and interpretation of meaning. The findings reveal that digital marketing is not merely perceived as a promotional tool, but as an interactive medium that facilitates emotional closeness and sustained engagement between the cafe and its customers. Customer experiences created through atmosphere, service quality, and consistent digital interaction contribute to a sense of belonging that encourages active participation within the community. The integration of online and offline experiences results in long-term relational bonds reflected in both digital and physical customer involvement. This study implies that experience-based and community-oriented marketing strategies are relevant approaches for culinary SMEs in building business sustainability.